Vacuolar Na+/H+ Antiporter Expression and Salt Tolerance Conferred by Actin1D and CaMV35S are Similar in Transgenic Binnatoa Rice (Plant Tissue Culture and Biotechnology, 2010)
Key words:  RT-PCR, ion imbalance, Binnatoa, transgenic plant  D.O.I. 10.3329/ptcb.v19i2.5444 Plant Tissue Cult. & Biotech. 19(2): 257-262, 2009 (December)       - Short communication